EFFECT ANALYSIS OF ROTATIONAL SPEED CHANGES ON PROPELLER TURBINES ON THE POTENTIAL FOR CAVITATION FORMATION USING COMPUTATIONAL FLUID DYNAMIC METHOD (CFD) - Widodo, Aditya Putra; Khaerudini, Deni Shidqi (Universitas Mercu Buana, 2024)
Water is an inexhaustible resource. In Indonesia there are several areas that have the potential of water energy for electricity production. Water energy can be used for electricity production and supports emission reduction programs because it does not produce CO2 emissions during the electricity production process by water turbines. One of the problems experienced by turbines is damage caused by cavitation. Cavitation itself is the formation of air gas bubbles due to very low pressure reaching below the vapor pressure, so that water evaporates at low pressure. This research was conducted to determine the effect of rotational speed on the potential for cavitation. This research was conducted using the CFD method and using the ANSYS application. In the simulation process, several variables are used, namely rotational speed and fluid velocity. The conclusion of this study is that the higher the rotating speed of a propeller turbine, the higher the cavitation potential that will occur in the propeller turbine. Because the higher the rotational speed of a turbine,so the lower the pressure that occurs in the turbine, this is in accordance with Bernoulli's Law. Suggestions for further research can be done with several modifications or variations of the winglet radius so as to get a better design. In addition, in future research it is also possible to modify the angle of the blade so as to reduce the emergence or formation of gas bubbles on the propeller blades due to decreased pressure.